2005
DOI: 10.1097/01.wnr.0000175244.51084.bb
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-isoform of Ca2+/calmodulin-dependent kinase II autophosphorylation is required for memory consolidation-specific transcription

Abstract: Autophosphorylation of the alpha-isoform of Ca2+/calmodulin-dependent kinase II switches the kinase into an autonomous activity mode. This molecular switch is important for hippocampal long-term memory formation, which requires de novo gene transcription and protein synthesis. Here, we have studied whether auto-phosphorylation of the alpha-isoform of Ca2+/calmodulin-dependent kinase II is required for gene transcription induced in the hippocampus by contextual fear conditioning. We have shown that upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…One such signaling molecule is CaMKII which is thought to be involved in changes in gene transcription and protein synthesis through its regulation of CREB (Wayman et al, 2008), a critical regulator of LTM formation and stability in the neurons (Josselyn et al, 2001; Han et al, 2007, 2008, 2009). Indeed, numerous studies have suggested that CaMKII is critical for LTM formation and that this requirement for CaMKII signaling overlaps with the requirement for protein degradation and synthesis during memory consolidation (Barros et al, 1999; Rodrigues et al, 2004; Von Hertzen and Giese, 2005; Halt et al, 2012; Da Silva et al, 2013). Collectively, these results suggest that changes in NMDAR and CaMKII activity correlate with changes in both protein degradation and protein synthesis during LTM formation in neurons.…”
Section: The Linking Of Protein Degradation and Synthesis Through Nmdmentioning
confidence: 99%
“…One such signaling molecule is CaMKII which is thought to be involved in changes in gene transcription and protein synthesis through its regulation of CREB (Wayman et al, 2008), a critical regulator of LTM formation and stability in the neurons (Josselyn et al, 2001; Han et al, 2007, 2008, 2009). Indeed, numerous studies have suggested that CaMKII is critical for LTM formation and that this requirement for CaMKII signaling overlaps with the requirement for protein degradation and synthesis during memory consolidation (Barros et al, 1999; Rodrigues et al, 2004; Von Hertzen and Giese, 2005; Halt et al, 2012; Da Silva et al, 2013). Collectively, these results suggest that changes in NMDAR and CaMKII activity correlate with changes in both protein degradation and protein synthesis during LTM formation in neurons.…”
Section: The Linking Of Protein Degradation and Synthesis Through Nmdmentioning
confidence: 99%
“…One or more members of this family are found in virtually every tissue, and mediate diverse physiological responses triggered by increases in intracellular calcium concentrations, activation by the binding of calcium/calmodulin and the ability to undergo autophosphorylation. CaMKII is expressed most abundantly in neurons, and is involved in regulating many aspects of neuronal function, including neurotransmitter synthesis and release, modulation of ion channel activity, cellular transport, cellular morphology and neurite extension, long-term plasticity, learning, memory consolidation, and memory erasure following retrieval [2][3][4][5][6][7]. Non-neuronal CaMKII has been implicated in the regulation of other biological processes, such as fertilisation [8], osteogenic differentiation [9], and the maintenance of vascular tone [10].…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of hippocampal NGFI-B mRNA expression after contextual fear conditioning is independent of sex and is not impaired in Camkk1 hypomorphic mutants. Like BDNF, nerve growth factor-inducible gene B is a CREB target gene and its hippocampal mRNA expression is up-regulated specifically by the learned association after contextual fear conditioning (50,51). We studied whether the up-regulation of hippocampal NGFI-B mRNA expression after contextual fear conditioning is also dependent on sex and whether it requires CaMKK␣ signaling (Fig.…”
Section: Vol 26 2006 Camkk␣ Plays a Complex Role In Memory Formatiomentioning
confidence: 99%